Company Characteristics, Internet Financial And Sustainability Reporting And Company Performance - James Tumewu; Siti Asiah Murni; Akhmad Zainuddin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to examine and analyze company characteristics and IFSR reporting on company performance. Company characteristics are measured using the board of commissioners, audit committee, industry type and company size, internet financial sustainability reporting (IFSR) is a type of voluntary expression, while company performance is measured using net profit margin (NPM). The research sample was 35 companies during 3 years of observation selected using purposive sampling, and the analysis technique used linear regression. The research results show that the board of commissioners and audit committee influence the company's performance, while the type of industry, internet financial and sustainability reporting and company size do not influence the company's performance.